PELATIHAN MENULIS CERITA ANAK EDUKATIF BAGI GURU SEKOLAH DASAR KOTA BANDAR LAMPUNG - Prasetya, Rian Andri; Trisna, Indah Nevira; Deviyanti, Rafista; Gustira, Yinda Dwi (Jurusan Pendidikan Bahasa dan Seni, FKIP Universitas Lampung, 2025)
The literacy skills of Indonesian children remain relatively low, while elementary school teachers play a crucial role in fostering reading interest and shaping students’ character through educational media such as children’s stories. However, many teachers still lack the ability to write engaging and meaningful stories that suit students’ psychological development. To address this issue, this community service program focuses on training elementary school teachers in Bandar Lampung to write educational children’s stories. The training aims to enhance teachers’ creativity and writing competence in producing stories that are not only entertaining but also instill character values such as honesty, responsibility, and cooperation. The activities are conducted through a participatory approach involving material presentation, writing practice, and mentoring sessions. The results indicate an improvement in participants’ understanding, skills, and positive attitudes toward writing educational children’s stories, as reflected in the comparison between pre- and post-training evaluations. Kemampuan literasi anak-anak Indonesia masih tergolong rendah, sementara guru sekolah dasar memiliki peran penting dalam menumbuhkan minat baca serta membentuk karakter siswa melalui media edukatif seperti cerita anak. Namun, banyak guru belum memiliki keterampilan menulis cerita anak yang menarik, bermakna, dan sesuai dengan perkembangan psikologis siswa. Untuk menjawab permasalahan tersebut, kegiatan pengabdian ini difokuskan pada pelatihan penulisan cerita anak edukatif bagi guru sekolah dasar di Kota Bandar Lampung. Pelatihan ini bertujuan untuk meningkatkan kreativitas dan kompetensi menulis guru dalam menghasilkan cerita anak yang tidak hanya menghibur, tetapi juga sarat nilai-nilai karakter seperti kejujuran, tanggung jawab, dan kerja sama. Kegiatan dilaksanakan melalui pendekatan partisipatif yang meliputi penyampaian materi, praktik penulisan, dan pendampingan. Hasil pelatihan menunjukkan adanya peningkatan pemahaman, keterampilan, serta sikap positif peserta terhadap penulisan cerita anak edukatif, yang tercermin dari perbandingan hasil evaluasi sebelum dan sesudah pelatihan.